Paediatric Nurses’ Attitudes towards and Knowledge of Breastfeeding - Miller, Joanne (2012)
Background Exclusive breastfeeding for six months is recommended by the World Health Organisation and the NHS. Mothers who are breastfeeding need the appropriate support and guidance from health professionals in order for them to continue breastfeeding. Staff on paediatric wards come into contact with many infants under the age of six months and therefore need a high standard of knowledge so that they can support and advise mothers on the ward appropriately. However evidence suggests that some health professionals do not have the knowledge to be able to support mothers. Method A survey questionnaire was distributed to nursing staff on the paediatric wards at Nottingham Children’s Hospital to assess their attitudes towards and knowledge of breastfeeding, along with their confidence levels when supporting mothers who are breastfeeding. The results were analysed using non-parametric statistical tests. Results Sixty-seven nursing staff out of 240 responded from twelve wards. There was a positive correlation between attitudes towards and knowledge of breastfeeding. Personal experience of breastfeeding was shown to increase knowledge and confidence when supporting mothers who were breastfeeding. There was no statistical difference between qualified nurses, care support workers or student nurses and attitudes towards and knowledge of breastfeeding or confidence levels. Conclusion The study highlighted that although knowledge was high, there were some gaps, and although attitudes towards breastfeeding were positive, there were some exceptions. Personal experience increased knowledge and confidence and therefore needs to be taken into consideration when creating a training programme for the staff. Ensuring training is given as part of an induction will help to increase new staffs knowledge and attitudes towards breastfeeding, as well as their confidence when supporting mothers who are breastfeeding which is crucial.